2014
DOI: 10.1186/1756-0500-7-880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8,000 IU aXa long-term prophylaxis with certoparin on the incidence of hyperkalemia in patients with coronary heart disease – a post-hoc analysis of the PARAT trial

Abstract: BackgroundHyperkalemia is an infrequent but potentially serious complication of low molecular weight heparin (LMWH) use. While there are a number of trials comparing LMWH to unfractionated heparin (UFH) there is no comparison of the risk with LMWH versus placebo. Aim of the present post-hoc analysis of the PARAT trial was the description of serum potassium levels with certoparin compared to placebo.ResultsPARAT was a double-blind, placebo-controlled, randomized trial in patients with coronary artery disease re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Melzer et al. [13] reported 12 cases of hyperkalemia. However, this was likely attributed to other medications, as the patients were also taking ACE inhibitors and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melzer et al. [13] reported 12 cases of hyperkalemia. However, this was likely attributed to other medications, as the patients were also taking ACE inhibitors and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…ACE inhibitor use and baseline potassium were linked in their analysis. Melzer et al [13], reported 10 cases of hyperkalemia, however it was probably linked to the other drugs as the patients were taking ACE inhibitors, and NSAIDS Rocha et al [18] found no hyperkalemia with bemparin but 4 cases with UFH. Koren-Michowitz et al…”
Section: Potassiummentioning
confidence: 99%